Exploring the Integration of Engineering Design Practices in Tenth-Grade Chemistry Activities - Aldahmash, Abdulwali H.; Alfarraj, Yousef F. (Frontiers in Psychology, 2022)
Chemistry textbooks are the most popular teaching material in schools. They can contribute significantly to the attainment of scientific educational goals. Globally, educational reforms in science subjects are adopting newer practices such as engineering design processes (EDP) for addressing real-world requirements. This study, conducted in Saudi Arabia, employed a qualitative and quantitative content analysis method to evaluate the level of the EDP incorporated in the tenth-grade chemistry textbook and accompanying student’s experiments´ guidebook. The results found the inclusive mean for EDP was 1.05, which indicated incorporation at level one. This inclusion has been rated as novice or deficient, which indicates that it does not fulfill the majority of the requirements for inclusion as suggested by NGSS.